Diversidade genética e análise dialélica em coentro (Coriandrum sativum L.) - Wanderley, Katyanne Maciel (2023)
In Brazil, coriander is used as a seasoning on a large scale. It is possible that, in terms of market value, it is the second most important leafy vegetable in the country. It is cultivated throughout the year and by many producers, playing a significant social role, especially in the North and Northeast regions of Brazil. This species presents diversity for size, flower and fruit characteristics, which gives it different potential uses. In addition to the large consumption in natura, they are also used for the extraction of essential oils with high added value, used in the flavoring, cosmetics and medicine industries. Due to their great genetic variability, it grants the species potential for use in genetic improvement. Thus, knowledge of the diversity among individuals makes it possible to arrange genotypes in groups, which, when intercrossed, can obtain greater heterosis results. The genotypes can be crossed and evaluated using the diallel analysis methodology, with those of Griffing (1956), Gardner and Eberhart (1966) and Hayman (1954) being the most used. Thus, the objective was to evaluate the genetic diversity among coriander (Coriandrum sativum L.) parents, perform diallel crosses and determine the most promising ones. The experiment was carried out in an agricultural greenhouse in the Plant Biotechnology sector of the Center for Agricultural Sciences at the Federal University of Paraíba (CCA-UFPB). Nine coriander (C. sativum L.) parents were used, the design used was completely randomized. Data were subjected to analysis of variance, Scott-Knott mean test and estimated heritability. Genetic divergence was analyzed by Tocher's method, based on the generalized Mahalanobis distance and analysis of canonical variables with graphical dispersion of accessions. The relative importance of the variables was determined by the method described by Singh (1981) and by canonical variables. For the diallel analysis, 36 treatments (8 parents and 28 hybrids) with ten replications were used. The diallel analysis was performed to estimate the General Combining Ability (GCA) and Specific Combining Ability (CEC), according to Griffing's method (1956). To determine the heterosis and its components, the methodology of Gardner and Eberhart (1966) was used and to study the inheritance of morphoagronomic characteristics, the methodology of Hayman (1954) was used. It was verified the existence of phenotypic divergence between the parents of C. sativum L., being able to be used in programs of genetic improvement of coriander. Verdão, Rei, Leisure 06, Duradero and Tabocas genotypes were selected. The results showed that for the characteristics of seedling, plant, flower and fruit, there was influence of additive and non-additive effects, with superiority for additive effects. The hybrids Tabocas x Verdão (2x6), Tabocas x La Reina Baja (2x4), Purple x Rei (1x7), Verdão x Calypso (6x8), Tabocas x La Reina Baja (2x4), Cilantro x Verdão (3x6), La Reina Baja (4x6), Verdão x Rei (6x7), La Reina Baja x Rei (4x7), Tabocas x Rei (2x7), Purple x Tabocas (1x2) and Duradero x Verdão (5x6) can be used to continue the training program improvement. There is diversity among the studied accessions, with significant effects of heterosis and its components. There are possibilities of genetic gains, via breeding programs, referring to plant, flower and fruit characteristics in coriander and the Purple, Verdão and Rei genotypes showed the highest concentration of favorable alleles for size, flower and fruit characters.